Next nature : edited and designed by Koert van Mensvoort and Hendrik-Jan Grievink - Grievink, Hendrik-Jan , 1977-; Mensvoort, Koert van (Barcelona, Spain : Actar Birkhauser, 2011)
Exploring human impact on nature
Includes index
Keywords: Nature -- effect of human being on; Nature -- social aspects; Technology -- Social aspects